Living Plans : New Concepts for Advanced Housing - Gast, Klaus-Peter (Basel, Berlin [etc.] : Birkhäuser, 2005)
Living in a small area : Rural : House on Tinos, Greece / Pantelis Nicolacopoulos ; A+B House, Austria / Oskar Leo Kaufmann ; House in the Alps, Switzerland / Roberto Briccola / Gaspar House / Alberto Campo Baeza -- Village : Steinhauser Boathouse, Austria / Marte.Marte ; House in Mukarov, Czech Republic / Ivan Kroupa -- Urban : Nomi House, Japan / Tadao Ando ; TN House, Japan / Koh Kitayama and Architecture Workshop ; Tofu House, Japan / Jun Tamaki ; T-set House, Japan / Chiba Manabu-- Classical living : Rural : Carter/Tucker House, Australia / Sean Godsell ; GA House, India / Klaus-Peter Gast ; Peninsula House, Australia / Sean Godsell ; House in Moledo, Portugal / Eduardo Souto de Moura ; Burger House, Austria / Baumschlager & Eberle ; House in Röthis, Austria / Ivan Cavegn ; House in Nagasaki, Japan / Hiroshi Hara ; Gobhai House, India / Charles Correa -- Village : ST House, Italy / Liverani/Molteni ; 4 x 4 House, Japan / Tadao Ando ; Red House, Norway / Jarmund/Vigsnæs ; House at Mt.Fuji, Japan / Satoshi Okada ; House in Kleinmachnow, Germany / Oikos-Herrlee und Stoll ; 9 x 9 House, Germany / Titus Bernhard ; Spindler House, Germany / Robert Beyer ; Reinert House, Germany / Becher + Rottkamp ; Tiemann House, Germany / Dierks-Kunze-Oevermann ; Asencio House, Spain / Alberto Campo Baeza ; Marte House, Switzerland / Marte.Marte ; House in Altach, Austria / Markus Thurnher ; Hoffmann House, Germany / Becher + Rottkamp ; Baden House, Germany / Manfred Nagel ; House in Černosiče, Czech Republic / Ivan Kroupa ; Ulmer House, Austria / Baumschlager & Eberle ; Jordí Cantarell House, Spain / Jubert + Santacana ; House in Degerloch, Germany / Schlude + Ströhle ; House in Almelo, Netherlands / Dirk Jan Postel ; Nadonly House, Switzerland ; Morger & Degelo ; Turegano House, Spain / Alberto Campo Baeza -- Urban : House in black, Japan / Chiba Manabu ; Herrera House, Spain / José Morales and Juan Gonzáles Mariscal ; Hakuei House, Japan / Akira Sakamoto
boek